Marketing Effectively - Ali, Moi. (London : Dorling Kindersley, 2001)
The titles in the Essential Managers series provide accessible coverage of the key skills needed to succeed in business. They contain hints and tips, checklists, diagrams and photographs.
Includes index.
Keywords: Marketing; Marketing -- Management; Business and Management